Turkish language teacher candidates’ thoughts on e-readers, digital reading, and reading preferences - Münire Özden; Mehmet Çiçek (Anadolu Üniversitesi Eğitim Fakültesi dergisi, 2025)
This research aims to determine teacher candidates’ thoughts, experiences, and expectations about digital reading and e-readers and examine students' reading habits comprehensively. The research study group consists of 116 teacher candidates studying in the Turkish Language Teaching program. This qualitative research investigated many important factors, such as students' daily reading time, digital and traditional reading preferences, the software they use in digital reading, e-readers, and the reasons for preferring these devices. The study's findings were made more meaningful by comparing the data obtained with other studies in the literature. The study results show that students prefer digital platforms, but using e-readers is less common than using digital applications. However, it was concluded that students prefer reading from printed sources to reading from digital tools. This indicates that printed books are still a strong preference and that students face some barriers in transitioning to digital reading tools. Regarding the interest and usage rate of e-readers, it is understood that students mostly prefer printed books, and it will take time for their digital reading habits to develop. Furthermore, the study concluded that digital reading tools and e-readers may not be equally effective or important for all users. This shows that digital reading habits may vary according to the user's preferences, age, technological predisposition, and reading habits. In this context, it can be said that design, accessibility, and ease of use should be considered for digital reading tools to appeal to a broader user base.